Pollution Problems in Koya City due to Private Electrical Generators - Abbas, Hayder H.; Ibraheem, Fakhri H.; Maaroof, Ahmed A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Koya city, like any other city in the world, faces a critical environmental problem which is global warming and the increase in the rate of production of gaseous pollutants. This research is involved with the negative effects of private Electrical Power Generators (EPGs) on the environment in Koya City. The environmental pollutants resulted from EPGs were investigated by performing an actual study on land for the number of (EPGs), types, and distribution. Koya city is divided into 18 quarters. The investigation covers a period from 2009 to 2017, included. The production of power was increased due to the increase in the number of generators and supplying hours. The power production in 2009 was 23,850 megawatt (MW) whereas it was 49,635 MW in 2017. The amount of fuel consumed in 2009–2017 was relatively increased from 30,000 to 62,500 barrel/year. The total amount of pollutants was increased by about 108% during the period 2009–2017. The results showed that the most significant increase in pollutants was carbon dioxide (CO2). The annual amount of (CO2) emitted in 2009 was 6588 tons whereas it has increased in 2017–13710 tons. The conclusion of this study was that the highest pollution occurred in the center of Koya City in Nabeel quarter, which represented 22% of the whole pollutants.